AMP and Ambersep 920 IRA anion exchange resins for recovery of uranium from productive solution - Nursapina, Nurgul Armankyzy; Matveyeva, Ilona; Shynybek, Balnur (International Journal of Biology and Chemistry, 2018)
In the process of uranium production, one of the most important stages affecting the completeness of uranium extraction from productive solutions is the sorption stage. In order to study the effectiveness of ion exchange resins under dynamic conditions, sorption and desorption characteristics of anion exchangers, which used for recovery of uranium from sulfuric acid production solutions were studied. In laboratory conditions, sorption and desorption of uranium from productive solution on anion exchange resins of the brands Ambersep 920 IRA and AMP were carried out. During the research work, sorption and desorption characteristics were studied, as well as sorption capacity of the resins. Despite the fact that dynamic exchange capacities of the resins are equal, the sorption characteristics are different. The concentration of uranium in the desorption eluate for Ambersep 920 IRA and AMP was 856.00 and 268.00 mg/l, respectively, which is 5 and 1.5 times higher than the initial concentration of uranium in the productive solution. The most efficient anion exchanger, Ambersep 920 IRA, has been identified, which has good sorption and desorption characteristics compare to AMP.